2016
DOI: 10.2298/tsci16s5203l
|View full text |Cite
|
Sign up to set email alerts
|

Industrial cooling tower design and operation in the moderate-continental climate conditions

Abstract: A large number of producers offer a wide choice of various types of industrial cooling towers. Usually, a proper choice of pre-fabricated cooling tower satisfies end-user needs. However, if there are specific end-user requirements, it is necessary to design cooling tower according to those requirements. For the adhesive factory located in southern region of Serbia, 350 kW mechanical draught wet cooling tower was designed and built. Dimensioning of the cooling tower was done according to param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…• Estimation of the technical performance of present equipment and an analysis of the opportunities to improve their efficiency • Improving the maintenance procedures • Implementing new proven technology in the current energy system • Increase capacity of the existing cooling tower • Install a new tower The effect of climatic changes is shown to be important in the design of more effective cooling technique and to device methods to compensate for the loss in plant efficiency. 4 Lakovie et al 5 showed that dimensioning a cooling tower according to ambient air parameters that are higher than current standard recommendations ensures required cooling water temperature for efficient plant operation and gives experimental confirmation for this statement.…”
Section: Introductionmentioning
confidence: 92%
“…• Estimation of the technical performance of present equipment and an analysis of the opportunities to improve their efficiency • Improving the maintenance procedures • Implementing new proven technology in the current energy system • Increase capacity of the existing cooling tower • Install a new tower The effect of climatic changes is shown to be important in the design of more effective cooling technique and to device methods to compensate for the loss in plant efficiency. 4 Lakovie et al 5 showed that dimensioning a cooling tower according to ambient air parameters that are higher than current standard recommendations ensures required cooling water temperature for efficient plant operation and gives experimental confirmation for this statement.…”
Section: Introductionmentioning
confidence: 92%
“…Thermal effectiveness of cooling tower is expressed as a ratio of cooling range and sum of cooling range and approach. It can also be represented as actual temperature difference of cooling water as it flows through the cooling tower and a maximum theoretical temperature difference [7,8]:…”
Section: Thermal Effectiveness Cooling Range and Approachmentioning
confidence: 99%
“…Effectiveness by eq. (6) Effectiveness by [6] Effectiveness by designed data Air wet bulb temperature by [6] Air wet bulb temperature It is shown that effectiveness of cooling of the water film depends on the ratio of water to air mass-flow rates and decreases while ratio increase [8]. During the measurement, ratio of mass-flow rates was preserved in approximately constant values around 1.064, so this effect was not tested.…”
Section: Thermal Effectiveness Cooling Range and Approachmentioning
confidence: 99%
See 1 more Smart Citation